Comparison and Validation of Three Soybean Phenology Models - Peltzer, Hugo (2016)
Temperature and photoperiod regulate the duration of soybean development stages. Photothermal sensitivity varies between the genotypes, being higher in long-cycle cultivars compared with short-cycle ones. Temperature and photoperiod also vary according to geographic location (latitude) and time of the year (sowing season), generating a complex genotype-environment interaction. This interaction makes it difficult to predict crop phenological stages. A simulation model to predict the date of occurrence of these phenological stages is very useful for decision-making in crop management. In this work, we compared and validated three empirical models for simulating soybean phenology stages. The three models presented in this paper are in commercial phase under the brand SIFESOJA.